TAXATION OF CENTRALISED DRINKING WATER SUPPLY SERVICES WITH VALUE-ADDED TAX - Kavun, A. (Municipal economy of cities. Series: «Economy science», 2024)
The scientific article is devoted to the issue of reducing the tax burden on such a socially important service as a centralised drinking water supply. The study has determined that the service of centralised drinking water supply is an essential component on the way to achieving universal and equal access to safe and affordable drinking water for everyone in Ukraine. The research shows that the legal form of the utility company as a service provider is the most common for providing water supply services. This form best allows local self-government bodies to conduct their tasks and obligations in the drinking water supply. The study revealed the main features of the water supply service. We established that the service has great social significance and that its main task is not to make a profit but to provide consumers with quality drinking water in sufficient quantity and at an acceptable cost level. Despite its significant social value, the drinking water supply services are subject to value-added tax at the usual rate of 20%. The study found that the drinking water supply services generate significant added value, which results in service providers paying substantial amounts of value-added tax to the state budget. We concluded that such a situation does not correspond with the spirit of providing the population with drinking water and is unacceptable for a heavily subsidised service with many chronic problems, including high levels of deterioration of water supply infrastructure and low coverage of rural areas with centralised water supply. Further, we carried out an analysis of the legislation of the European Union regarding the taxation of water supply services with value-added tax. We determined that most countries of the European Union use the practice of applying a reduced value-added tax rate for the taxation of water supply services. The obtained results justify the further necessity to study the issue of making changes to the tax legislation of Ukraine to apply a reduced value-added tax rate or complete exemption from taxation of the value-added tax for centralised drinking water supply services.